Persepsi Orang Tua terhadap Pemberian Tugas berbasis Pembelajaran Daring bagi Anak Kelompok B di TK Kecamatan Srono Banyuwangi - Ulin Tegarinfisa; Hendratno Hendratno; Sri Setyowati (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2021)
The purpose of this study was to determine the parents' perception of the assignment based on online learning. The impact of the Covid-19 pandemic is felt by various fields, including the field of education. The implementation of online-based learning in giving assignments for early childhood has its own challenges and still requires online assistance and support from parents. This research is quantitative research. The sample in this study were group B children who were attending Khadijah 58 Kindergarten, amounting to 51 people. The results obtained in this study indicate that the parent's perception of the assignment based on online learning with a p-value < 0.005. The conclusion of this study is that there are significant differences in parental perceptions of the assignment of online learning-based tasks.